2016
DOI: 10.5539/elt.v9n3p181
|View full text |Cite
|
Sign up to set email alerts
|

Situational Variations in Request and Apology Realization Strategies among International Postgraduate Students at Malaysian Universities

Abstract: <p>The present study attempted to describe the request, apology, and request mitigation strategies utilized by international postgraduate students in confronting different situations. In addition, it examined the effects of the situational factors of social distance, power, and imposition on the students’ choice of request and apology strategies as well as the modifications in requests. Another objective has been to categorize the difficulties students face in the production of the speech acts. One hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…And this result is partially in agreement with (Muthusamy and Farashaiyan, 2016) who concluded the use of conventionally indirect expressions (preparatory questions) is preferred for requests more often than other expressions, regardless of power, the social distance and imposition, where request strategies affected the use of mitigating strategies in different situations. There is something that we should consider that social distance and power play a significant role in affecting the speech request strategies.…”
Section: Discussionsupporting
confidence: 87%
“…And this result is partially in agreement with (Muthusamy and Farashaiyan, 2016) who concluded the use of conventionally indirect expressions (preparatory questions) is preferred for requests more often than other expressions, regardless of power, the social distance and imposition, where request strategies affected the use of mitigating strategies in different situations. There is something that we should consider that social distance and power play a significant role in affecting the speech request strategies.…”
Section: Discussionsupporting
confidence: 87%
“…Finally it is also found that YTs often used conventionally indirect strategy in doing request regardless the specific context of communication. Such a finding confirms Muthusamy and Farashaiyan (2016) who concluded their study that the use of conventionally indrect strategy (preparatory questions) is more ferquently used, regardless of the power, the social distance and imposition, where the request strategies affected the use of mitigating strategies in different situations [13] [14].…”
Section: 35supporting
confidence: 76%
“…Another study was conducted by Muthusamy and Farashaiyan (2016) on request, apology, and request mitigation strategies used by one hundred and thirty international postgraduate students specializing in different domains. The results showed that the participants used conventionally indirect expressions (preparatory questions) for requests more often than other expressions.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%